2021
DOI: 10.1080/2162402x.2021.1908771
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunotherapy with ipilimumab and nivolumab in patients with advanced adrenocortical carcinoma: a subgroup analysis of CA209-538

Abstract: Background : Adrenocortical carcinoma is a rare malignancy, with poor prognosis and limited treatment options for patients with advanced disease. Chemotherapy is the current standard first-line treatment, providing only a modest survival benefit. There is only limited treatment experience with immunotherapy using single-agent anti-PD-1/PD-L1 therapy. To date no clinical trials have been reported using combination immunotherapy with anti-CTLA-4 and anti-PD-1 blockade in this patient population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In ACC, a limited number of mostly small prospective trials with CPI therapy have been performed. These studies demonstrated relatively low efficacy [2][3][4][5][6]. The largest and most recent retrospective analysis reported objective response rates of 13.5 % to immune checkpoint blockade in ACC [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ACC, a limited number of mostly small prospective trials with CPI therapy have been performed. These studies demonstrated relatively low efficacy [2][3][4][5][6]. The largest and most recent retrospective analysis reported objective response rates of 13.5 % to immune checkpoint blockade in ACC [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are open questions whether mitotane can induce immunogenic cell death and if synchronous combination of mitotane with CPI may adversely impact the antitumoral immune response. Of note, mitotane treatment was permitted in some but excluded in other published trials of immunotherapy in ACC [2][3][4][5][6]. However, this did not explain the different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… [ 29 ] Biliary tract carcinomas 3 mg/kg of nivolumab and 1 mg/kg of ipilimumab every 3 weeks for 4 doses, followed by nivolumab 3 mg/kg every 2 weeks and continued for up to 96 weeks until disease progression NCT02923934 39 Some had chemotherapy The ORR was 23% ( n = 9) with a disease control rate of 44% ( n = 17) Responders were patients with intrahepatic cholangiocarcinoma and gallbladder carcinoma. 49% of patients ( n = 19) had immune related toxic effects of which 15% ( n = 6) were grade 3 or 4 [ 30 ] Adrenocortical carcinoma 200 mg of pembrolizumab intravenously every 3 weeks until disease progression or intolerance 15 Yes NPR at 27 weeks was 31%, ORR 15%, and CBR 54% [ 19 ] Adrenocortical carcinoma nivolumab (3 mg/kg IV) and the anti-CTLA-4 antibody ipilimumab (1 mg/kg IV) every three weeks for four doses, followed by nivolumab (3 mg/kg IV) every two weeks and continued for up to 96 weeks 6 Yes PR 33%, SD 33% [ 31 ] Paraganglioma–pheochromocytoma 200 mg of pembrolizumab intravenously every 3 weeks until disease progression or intolerance 9 Yes NPR at 27 weeks was 43%, ORR 0%, and CBR 75%. [ 19 ] Pleural mesothelioma Patients were administered nivolumab (240 mg every 2 weeks) and ipilimumab (1 mg/kg every 6 weeks up to four times) intravenously.…”
Section: Immune-based Therapeutic Approaches and Their Current Status...mentioning
confidence: 99%
“…Like hepatobiliary cancers, adrenal cortical carcinoma (ACC) is associated with a dismal prognosis, and there are limited viable treatment options. Naing et al [19] and Klein et al [31] reported modest efficacy of single agent (pembrolizumab) or dual agent (nivolumab and ipilimumab), respectively, for patients with advanced ACC. These trials had small cohorts of 15 or less patients.…”
Section: Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…[7][8][9] CA 209-538 was a multicenter multicohort phase II trial that investigated combination immunotherapy with the anti-PD-1 antibody nivolumab and the anti-CTLA-4 antibody ipilimumab in patients with rare cancers. [10][11][12] The trial included a cohort of patients with METHODS: PATIENTS Study design, patients and treatment CA 209-538 was a multicenter open-label phase II study conducted at five Australia sites (Austin Health, Peter MacCallum Cancer Centre, Monash Health, Melbourne, Blacktown Hospital, Sydney, Border Medical Oncology, Albury). Eligible patients for the gynecological cohort were aged 18 years or older and had a histologically confirmed metastatic rare cancer of the female genital tract.…”
Section: Introductionmentioning
confidence: 99%